Analysis of carbide tool wear during turning of aisi 4340 with variations in cutting speed - Howard, A.; Rosehan, R.; Lubis, S.Y. (Dinamika Teknik Mesin, 2025)
This research aims to analyze the wear value of carbide cutting edges when used in the process of cutting AISI 4340 workpieces using a lathe. AISI 4340 is an alloy steel that is often used in the manufacturing industry because of its high strength and wear resistance. However, cutting in these materials can cause significant wear on the tool blade, which can affect the performance and service life of the cutting tool. The experimental method was carried out using a conventional lathe and a carbide cutting tool suitable for cutting alloy steel. A series of cutting tests were conducted with varying cutting speeds, while keeping the depth of cut and feed rate constant. The cutting parameters are as follows: varying cutting speeds of 141 m/min, 220 m/min, and 351 m/min, with a constant feed rate of 0.16 mm/rev and a fixed depth of cut of 0.5 mm for all cutting speed variations. It is shown that the carbide tool wear of 0.3 mm is reached at different times of each cutting speed. Data obtained from cutting tests are used to analyze the level of wear on carbide cutting edges and the factors that influence it. It is hoped that the results of this research will provide a better understanding of the interaction between the carbide cutting edge and the AISI 4340 workpiece during the cutting process.